2018
DOI: 10.1177/0091415018757211
|View full text |Cite
|
Sign up to set email alerts
|

Biological, Psychological, and Social Predictors of Longevity Among Utah Centenarians

Abstract: Studies of longevity among centenarians examine biological, psychological, and social factors, yet few consider these components concurrently. This study explores such factors individually and collectively, as they are related to days lived past the age of 100 years. Data from 268 family members of centenarians identified in the State of Utah between 2008 and 2015 were used in negative binomial models predicting number of days lived among the centenarians. Findings suggested that sleep latency (biological), li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Health behaviors related to improvements in HRV are similar to those that characterize the lifestyle of centenarians in different populations: regular physical activity, dietary habits, no drinking, and no smoking (Ozaki et al, 2007;Kim et al, 2012;Wu et al, 2017). But psychological moments are also a key element in the NIACT framework, and in the same way, active engagement in community activities, high levels of self-perceived well-being, and satisfaction with life are defining elements of the centenarian population (Ozaki et al, 2007;Kim et al, 2012;Wu et al, 2017;Hitchcott et al, 2018;Yorgason et al, 2018). Therefore, the characteristic lifestyle of centenarians would imply a greater resilience, indexed by greater variability of the HR and, as described above, higher SDNN values would mean better survival prognosis in centenarians.…”
Section: Centenarians and The "Neurovisceral Integration Across A Conmentioning
confidence: 96%
“…Health behaviors related to improvements in HRV are similar to those that characterize the lifestyle of centenarians in different populations: regular physical activity, dietary habits, no drinking, and no smoking (Ozaki et al, 2007;Kim et al, 2012;Wu et al, 2017). But psychological moments are also a key element in the NIACT framework, and in the same way, active engagement in community activities, high levels of self-perceived well-being, and satisfaction with life are defining elements of the centenarian population (Ozaki et al, 2007;Kim et al, 2012;Wu et al, 2017;Hitchcott et al, 2018;Yorgason et al, 2018). Therefore, the characteristic lifestyle of centenarians would imply a greater resilience, indexed by greater variability of the HR and, as described above, higher SDNN values would mean better survival prognosis in centenarians.…”
Section: Centenarians and The "Neurovisceral Integration Across A Conmentioning
confidence: 96%
“…The most obvious explanation of these differences is that socio-economic status impacts on nutritional profile, stress and exposure to infections, but recent data showed that epigenetic modifications (and in particular DNA methylation) may "recode" information of the father's environmental exposure and then be transmitted to the offspring [105][106][107] , supporting the crucial role of evaluating these factors for the missing heritability. Moreover, it has been suggested that -even if social interactions tend to reduce during aging -the maintenance of social connections help to live longer 108 and is associated with lower mortality.…”
Section: The Genetics Of Longevity In Different Socio-economic Settingsmentioning
confidence: 99%
“…In a unique study on centenarians, data were collected from 268 family members [41]. Sleep onset latency along with life satisfaction and attachment closeness were contributors to the number of days lived.…”
Section: Early Mortalitymentioning
confidence: 99%